Students' Preferences of Oral Corrective Feedback (OCF) in an EFL Class - Nurul Akidah Kidah; Muhammad Tahir; Munir (International Journal of Language, Education, and Literature, 2025)
This study investigates the types of oral corrective feedback (OCF) most preferred by students at SMK Negeri 1 Bone, focusing on their perceptions of various feedback methods in English as a Foreign Language (EFL) classrooms. The objective of the research is to identify which types of OCF are most effective and favored, contributing to improving teaching strategies in language learning. A quantitative research design was employed, using a structured questionnaire adapted from Bulbula (2020) to collect data from 60 students. The questionnaire included Likert-scale items ranging from 1 (strongly disagree) to 5 (strongly agree), evaluating six types of OCF: explicit correction, recast, metalinguistic feedback, clarification requests, elicitation, and repetition. The data were analyzed using SPSS version 29 to calculate descriptive statistics, including mean, standard deviation, and variance. The findings indicate that recast is the most preferred type of feedback, with the highest mean score (4.73–4.75), as its implicit nature promotes emotional safety and reduces anxiety. Repetition is also highly favored (mean: 4.15–4.17) for its ability to provide opportunities for self-correction in a supportive environment. In contrast, explicit correction (mean: 2.53), metalinguistic feedback (mean: 2.18), and elicitation (mean: 2.23–2.25) are less preferred due to their potential to cause anxiety or confusion. Clarification requests receive moderate favorability (mean: 3.53–3.55), encouraging critical thinking but requiring careful implementation to avoid stress. The study concludes that implicit feedback methods, such as recast and repetition, are more effective in fostering a positive learning experience. It recommends that educators prioritize these methods to enhance student confidence and engagement while ensuring the feedback aligns with students’ proficiency levels and needs. Future research could explore the long-term impact of preferred OCF methods on language acquisition and performance.